Behavior of steel columns with double curvature: a numerical simulation and design-oriented parametric study (Fracture and Structural Integrity, 2025)
This research present a novel investigation, which focuses on the numerical exploration of steel columns having a double curvature, built with both hollow square and circular cross-sections. A finite element model was initially created using ABAQUS software and was validated through a series of compression experiments conducted on square hollow specimens exhibiting double curvature. close agreement was observed in term of ultimate loads, load–displacement curves and deformed shapes corresponding to the failure modes. Based on validated numerical simulations, parametric analyses are carried out to investigate the effects of major geometric parameters on the axial bearing capacity of double curved steel columns. The study consists in a systematic variation of curvature angle (20°, 25°, 30°, and 35°), curvature radius (500 mm, 700 mm, 900 mm, and 1100 mm), square cross-section size (250 mm, 300 mm, 350 mm, and 400 mm), circular diameter (318 mm, 381 mm, 445 mm, and 509 mm) and end offset distance (400 mm, 600 mm, 800 mm, and 1000 mm). The findings highlighted the sensitivity of axial performance to angle curvature, section width and offset distance at column ends. The outcomes of this study provide valuable insights for the design and optimization of curved steel columns in structural engineering applications, particularly where stability and axial strength are critical.
Keywords: Steel columns; Double curved columns; Axial load capacity; Failure mechanisms; Experimental analysis; Modeling